Space Cowboy Caleb and the night sky round-up learning about the night sky - Dybvik, Tina; Record, Adam (North Mankato, MN Picture Window Books, 2014)
Through the fantastical story of a young boy, text and illustrations introduce features of the night sky, such as stars, meteors, and phases of the moon"--Provided by publisher
Science
a gift from book africa
1 2 13
Keywords: Astronomy -- Juvenile literature; Meteors -- Juvenile literature